Hydrocele in infants: surgical evaluation - Moreira França, João Antônio; Rodrigues Guedes , Sabrina; de Sousa Marques , Crislaini; Coelho Chagas , Ana Gabryella; de Oliveira Cardoso, Lívia; Rodrigues Fernandes Duarte, Rodrigo; Augusto Santana Silva , Guilherme; Lacerda Ribeiro , Patrick; de Souza Martins, Gabriela; Arruda Prado Cavalcante, Thiago; Bárbara Cardoso da Silva, Thamires; Gonçalves Benevides , Jessica; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Introduction: Hydrocele in infants is a condition characterized by fluid accumulation in the scrotum, often seen in newborns. This disorder, although often benign and self-limited, may require evaluation and, in some cases, surgical intervention. Understanding the factors associated with hydrocele, its clinical presentation, and therapeutic approach are essential to ensure appropriate management. The medical literature discusses the prevalence and implications of hydrocele, as well as guidelines for surgical evaluation in persistent cases, highlighting the importance of early identification and timely intervention. Methodology: The research followed the PRISMA checklist guidelines, using databases such as PubMed, Scielo, and Web of Science. Five descriptors were used: "hydrocele," "infants," "surgical evaluation," "treatment," and "clinical outcomes." Inclusion criteria included articles published in the last ten years, studies focused on infants, and that addressed the surgical evaluation of hydrocele. Conversely, exclusion criteria included non-systematic reviews, articles that did not specifically address the pediatric population, and studies with incomplete data. Results: The analysis revealed that most cases of hydrocele in infants resolve spontaneously, but surgery is recommended in cases of persistent or symptomatic hydrocele. The literature highlighted the importance of careful clinical evaluation and consideration of the risks and benefits of surgery. The main outcomes observed included surgical complication rates and parental satisfaction with the results. Conclusion: Hydrocele in infants requires a careful approach, taking into account both the often self-limiting nature of the condition and the potential associated complications. Surgical evaluation should be performed carefully, based on clinical guidelines and the experience of the medical team. The systematic review highlighted the importance of an individualized approach to each case, ensuring better outcomes for patients and their families.